Oscillations in the first order non-linear systems with delay. I. Autonomous systems - Anh, Nguyen Dong; Khiem, Nguyen Tien (Vietnam Journal of Mechanics, 1990)
Contrary to the systems without delay, in the first order systems with delay may be an undraped oscillation, which is constructed in this paper by means of the asymptotic method. The elf-excited oscillations in the Duffing and Van-De-Pol systems are considered.